Pedro Páramo : diálogos en contrapunto (1955-2005) - Jiménez de Báez, Yvette; Gutiérrez de Velasco, Luzelena (Serie lenguajes y tradiciones, 2008)
The word materializes in "Pedro Páramo", the classic novel by Juan Rulfo published in 1955, which always and every time denies the effects of absolute power on social and human life. Fifty years later, in this book, 26 national and international voices decipher that writing from the present.